Bullet-shaped magnetosomes and metagenomic-based magnetosome gene profiles in a deep-sea hydrothermal vent chimney - Nakano, Shinsaku; Furutani, Hitoshi; Kato, Shingo; Kouduka, Mariko; Yamazaki, Toshitsugu; Suzuki, Yohey (Frontiers in Microbiology, 2023)
Magnetosome-producing microorganisms can sense and move towards the redox gradient and are intensively characterized in terrestrial and shallow marine sediments. However, given the difficulty in sampling, magnetotactic bacteria (MTB) are poorly explored in deep-sea hydrothermal fields. We collected a deep-sea hydrothermal vent chimney from the Southern Mariana Trough using a remotely operated submersible. Mineralogical and geochemical characterization of the vent chimney sample showed the internal iron redox gradient. Additionally, electron microscopy of particles collected by magnetic separation from the chimney sample revealed MTB cells with bullet-shaped magnetosomes, and there were minor occurrences of cubo-octahedral and hexagonal prismatic magnetosomes. Genome-resolved metagenomic analysis was performed to identify microorganisms that formed magnetosomes. A metagenome-assembled genome (MAG) affiliated with Nitrospinae had magnetosome genes such as mamA, mamI, mamM, mamP, and mamQ. Furthermore, a diagnostic feature of MTB genomes such as magnetosome gene clusters (MGCs), including mamA, mamP, and mamQ, was also confirmed in the Nitrospinae-affiliated MAG. Two lines of evidence support the occurrence of MTB in a deep-sea hydrothermal vent environment.